Phylogeny of Myxobolidae (Myxozoa) and the evolution of myxospore appendages in the Myxobolus clade - Liu, Yang; Lövy, Alena; Gu, Zemao; Fiala, Ivan (International journal for parasitology, 2019)
Genera Myxobolus Bütschli, 1882 and Henneguya Thélohan, 1892 (Myxobolidae) are specious myxozoan genera. They comprise nearly half of overall known myxozoan species diversity. A typical spore feature of Henneguya is the presence of two caudal appendages of the spore valves, which distinguishes them from species of the genus Myxobolus. Several Myxobolus spp., however, were reported to show aberrant spores with Henneguya-like caudal appendages. We found such aberrant spores in Myxobolus tsangwuensis and Myxobolus wulii. We studied the ultrastructure of M. wulii and Myxobolus oralis spores with caudal appendages by transmission electron microscopy (TEM). TEM of these aberrant spores revealed that their caudal appendages have the same ultrastructure as the appendages of Henneguya spp. Small caudal appendages of M. wulii spores observed only on TEM suggested that this character may be often overlooked and more Myxobolus species potentially have the ability to express the caudal appendages on the myxospore. In order to trace the evolution of this character, we performed broad phylogenetic analysis of all species of the family Myxobolidae which are available in GenBank including nearly 300 taxa. We found at least eight independent evolutionary origins of spores with two appendages, three origins of a single appendage and 12 apparent secondary losses of the spore projections. Therefore, genus Henneguya with typical two-tailed myxospores is polyphyletic, however a majority of its species has a common ancestor and groups in the second largest subclade of the Myxobolus clade. We also mapped the biological characteristics (host, site of infection and environment) of Myxobolidae species on the phylogenetic tree. We revealed an evident host-associated evolutionary pattern in all parts of the Myxobolus clade with a distinct and species-rich subclade containing almost exclusively species infecting species of the Order Cypriniformes.
Keywords: transmisní elektronová mikroskopie; Phylogeny; Phylogenetic analysis; zvířata; Microscopy, Electron, Transmission; fylogeneze; Spores, Protozoan; Character evolution; Henneguya; Animals; buněčné výběžky; Myxozoa; Cell Surface Extensions; Ultrastructure; spory protozoální; Myxobolus